Molecular candidates for cardiac stretch-activated ion channels - Reed,A; Kohl,P; Peyronnet,R (Global Cardiology Science and Practice, 2014)
The heart is a mechanically-active organ that dynamically senses its own mechanical environment. This environment is constantly changing, on a beat-by-beat basis, with additional modulation by respiratory activity and changes in posture or physical activity, and further overlaid with more slowly occurring physiological (e.g. pregnancy, endurance training) or pathological challenges (e.g. pressure or volume overload). Far from being a simple pump, the heart detects changes in mechanical demand and adjusts its performance accordingly, both via heart rate and stroke volume alteration. Many of the underlying regulatory processes are encoded intracardially, and are thus maintained even in heart transplant recipients. Over the last three decades, molecular substrates of cardiac mechanosensitivity have gained increasing recognition in the scientific and clinical communities. Nonetheless, the processes underlying this phenomenon are still poorly understood. Stretch-activated ion channels (SAC) have been identified as one contributor to mechanosensitive autoregulation of the heartbeat. They also appear to play important roles in the development of cardiac pathologies - most notably stretch-induced arrhythmias. As recently discovered, some established cardiac drugs act, in part at least, via mechanotransduction pathways suggesting SAC as potential therapeutic targets. Clearly, identification of the molecular substrate of cardiac SAC is of clinical importance and a number of candidate proteins have been identified. At the same time, experimental studies have revealed variable-and at times contrasting-results regarding their function. Further complication arises from the fact that many ion channels that are not classically defined as SAC, including voltage and ligand-gated ion channels, can respond to mechanical stimulation. Here, we summarise what is known about the molecular substrate of the main candidates for cardiac SAC, before identifying potential further developments in